Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) population ecology in citrus orchards: the influence of orchard age - Albertyn, Sonnica (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
Anecdotal reports in the South African citrus industry claim higher populations of false codling moth (FCM), Thaumatotibia (Cryptophlebia) leucotreta (Meyr) (Lepidoptera: Tortricidae), in orchards during the first three to five harvesting years of citrus planted in virgin soil, after which, FCM numbers seem to decrease and remain consistent. Various laboratory studies and field surveys were conducted to determine if, and why juvenile orchards (four to eight years old) experience higher FCM infestation than mature orchards (nine years and older). In laboratory trials, Washington Navel oranges and Nova Mandarins from juvenile trees were shown to be significantly more susceptible to FCM damage and significantly more attractive for oviposition in both choice and no-choice trials, than fruit from mature trees. Although fruit from juvenile Cambria Navel trees were significantly more attractive than mature orchards for oviposition, they were not more susceptible to FCM damage. In contrast, fruit from juvenile and mature Midnight Valencia orchards were equally attractive for oviposition, but fruit from juvenile trees were significantly more susceptible to FCM damage than fruit from mature trees. Artificial diets were augmented with powder from fruit from juvenile or mature Washington Navel orchards at 5%, 10%, 15% or 30%. Higher larval survival of 76%, 63%, 50% and 34%, respectively, was recorded on diets containing fruit powder from the juvenile trees than on diets containing fruit powder from the mature trees, at 69%, 57%, 44% and 27% larval survival, respectively. Bioassays were conducted to determine if differences in plant chemistry between fruit from juvenile and mature trees will have an impact on the susceptibility FCM to entomopathogenic nematodes (EPN), entomopathogenic fungi (EPF) and Cryptophlebia leucotreta granulovirus (CrleGV). No significant differences in the susceptibility of larvae reared on diets containing 15% fruit powder from juvenile and mature trees to EPN and EPF were recorded. Mortality of neonate larvae was significantly lower when placed on diets containing 15% fruit powder from mature trees (45% mortality) than diets containing 15% fruit powder from juvenile trees (61% mortality), after larvae ingested the lowest virus concentration tested, being 2 x104 OBs/ml. Data collected from field surveys showed significantly lower egg parasitism, virus infection of larvae and EPF occurrence in juvenile orchards than mature orchards. Egg parasitism was between 11% and 54% higher in mature orchards than juvenile orchards, with the exception of Mandarins during 2015, where egg parasitism was slightly higher in juvenile orchards, but not significantly so. A significantly higher proportion of larvae retrieved from mature orchards (7% of larvae) were infected with CrleGV than larvae retrieved from juvenile orchards (4% of larvae). A significantly higher occurrence of EPF was recorded in non-bearing and mature orchards, with 40% and 37% occurrence respectively, than in juvenile orchards, with 25% occurrence recorded. EPF occurrence in juvenile orchards increased significantly by 16% to 32% from the first to the third year of sampling. In contrast to results recorded in laboratory trials, similar or higher pest pressure in juvenile orchards than mature orchards did not always result in significantly higher levels of FCM damage under field conditions. FCM damage in juvenile orchards may have been lower than expected, as greater extremes of temperature and lower humidity were recorded in juvenile orchards, which would increase larval mortality. Results of this study showed that juvenile and mature orchards are significantly different and should be managed differently.
Keywords: Cryptophlebia leucotreta; Population biology; Insect populations; Orchards; Insect nematodes; Entomopathogenic fungi